Affect for Mothers and Others - Lénárt-Muszka, Zsuzsanna (Hungarian Journal of English and American Studies, 2020)
Book review: Lane, Julia and Eleonora Joensuu, eds. Everyday World-Making: Toward an Understanding of Affect and Mothering. Bradford, ON: Demeter P, 2018. 340 pages. ISBN 978-1-77258-140-9. Pbk. 34.95.